Masticatory efficiency before and after surgery in oral cancer patients: comparative study of glossectomy, marginal mandibulectomy and segmental mandibulectomy - Ohba, Hiroiku; Shinohara, Mitsuyo; Namaki, Shunsuke; Matsumoto, Mitsuhiko; Tanaka, Hiroshi; Koshikawa, Noriaki (Journal of Oral Science, 2004)
This study evaluated the effect of oral cancer surgery on masticatory efficiency. Masticatory efficiency was measured using the ATP absorption method. Eating ability was measured using a questionnaire. Two groups were employed as controls: The “normal occlusion group” consisted of subjects who had a complete set of natural maxillary teeth opposed to mandibular teeth, and the “unilateral occlusion group” consisted of subjects who had lost their molar and premolar teeth on one side of the mandible as a result of caries or periodontal diseases. Three treatment groups, each of 6 patients, were studied: a glossectomy group, a marginal mandibulectomy group and a segmental mandibulectomy group. There were no differences in masticatory efficiency between two control groups. Masticatory efficiencies of the three oral cancer treatment groups were lower than in the unilateral occlusion group, even 12 months after surgery. Masticatory efficiency of the glossectomy group was significantly higher 12 months after surgery compared with pre-surgery. Masticatory and eating abilities of the marginal mandibulectomy group and the segmental mandibulectomy were reduced at 3 and 6 months after surgery. The masticatory efficiency 12 months after surgery was higher in the marginal mandibulectomy group than the segmental mandibulectomy group, although the difference was not statistically significant. The self assessed eating ability 12 months after surgery was significantly higher in the marginal mandibulectomy group than the segmental mandibulectomy group. These results suggest that discontinuation of the mandible may lead patients to eat only foods that do not require a substantial amount of chewing. Hence, the quality of life of patients in the marginal mandibulectomy group was considered to be better than that in the segmental mandibulectomy group. (J. Oral Sci. 46, 113-117, 2004)